Optimizing Traditional Games as an Interdisciplinary Learning Tool: Impacts on Student Mental Health, Cultural Awareness, and Online Learning Integration in Primary School - Feri Budi Setyawan; Bahtiyar Heru Susanto; Izzatul Fajriyah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Despite increasing interest in traditional games as pedagogical tools, research remains limited in explaining their interdisciplinary value, their contribution to children’s social-emotional well-being, their cultural relevance, and their applicability in online learning. This study addresses these gaps by examining the use of traditional games in a private primary school in Central Java with 120 students aged 7–11. Using a mixed-methods design, it integrates survey data on engagement, stress, and cultural awareness with focus group and interview insights to capture students’ and teachers’ experiences. Findings reveal that traditional games foster a heightened sense of cultural identity and promote cooperative behavior among students, thereby improving interpersonal skills and cultural understanding. Simultaneously, certain games posed challenges for students with varying physical abilities or differing familiarity with cultural practices, which occasionally led to frustration or disengagement. In the context of online learning, integrating traditional games required adaptive strategies, highlighting both the potential for innovative, interactive digital activities and the limitations imposed by technological infrastructure and student readiness. These results underscore the multifaceted role of traditional games as a bridge between cultural education, mental well-being, and interdisciplinary learning, suggesting careful selection, adaptation, and scaffolding are essential to maximize their educational value while mitigating situational challenges. Keywords: cultural awareness, mental health, online learning integration, traditional games